Role of computed tomography in the diagnosis and treatment of endodonto-periodontal lesion (LLC "Endo Press", 2020)
Combination of periodontitis and caries complications of dentoalveolar segment which is called endodonto-periodontal lesion is one of the most complicated pathology because of the difficulties of correct diagnosis and treatment. Using only intraoral X-ray, orthopantomography can lead to doctor's mistakes, and afterwards - complications after the treatment. Using computed tomography allows to find out anatomical features of root canals, to determine the location of root furcations, additional canals, to evaluate condition of periodontium. Thorough clinical diagnosis and using computed tomography allows doctor to assess the prospects for the treatment planning and dynamic monitoring, and the most valuable thing - to improve the quality of treatment.